The Creation of Nyanyian Layonsari Opera - I Gusti Ngurah Wiryawan Budhiana (IJCAS (International Journal of Creative and Arts Studies), 2020)
ABSTRACTThe creation of Nyanyian Layonsari was started with the writer's anxiety as a musician. In his journey as a cellist and conductor, he plays many works originating from Western Classical composers. In concerts, he rarely plays works originating from Indonesian composers; even it can be said to have never played them. From that experience, the writer wants to make a composition which has a characteristic. Nyanyian Layonsari is inspired by Geguritan Jayaprana which comes from North Bali. This work tells the story of the love tragedy between Jayaprana and Layonsari. The drama begins when Raja Kalianget falls in love with Layonsari, Jayaprana's wife, and wants to marry her. The story in this opera ends tragically when all are killed and all destroyed. The uniqueness of the story is on the atmosphere of sadness in the beginning when an outbreak of disease occurs, and it ends with the sadness too when all is destroyed. The Jayaprana and Layonsari stories are full of moral messages. In the creating process of Nyanyian Layonsari, the idioms of Balinese music were used, namely, kotekan, beetle sound effect “ngisep”, and “kajar” sound effect. In addition to Balinese musical idioms, nine-note synthetic scales were also used which were based on and inspired by the pelog and slendro harmony. The elements of music were processed based on the understanding of Western music theories. Through this staging opera, it is expected to convey the messages contained in the story and can be understood by the audiences. Besides, the creation of Nyanyian Layonsari Opera can bring a distinctive musical style and can be used as a development in the field of music composition in Indonesia, and can be raised in international forums.  Penciptaan Opera Nyanyian Layonsari ABSTRAK Penciptaan Nyanyian Layonsari dimulai dari kegelisahan penulis sebagai musisi. Dalam perjalanannya sebagai pemain cello dan kondakter, banyak memainkan karya-karya yang berasal dari komponis Klasik Barat. Dalam konser-konser jarang sekali memainkan bahkan bisa dikatakan tidak pernah memainkan karya yang berasal dari komponis Indonesia. Dari pengalaman itu penulis ingin membuat komposisi yang memiliki ciri yang khas. Nyanyian Layonsari bersumber dari Geguritan Jayaprana yang berasal dari Bali Utara. Karya ini mengisahkan tentang tragedi cinta antara Jayaprana dan Layonsari. Tragedi dimulai ketika Raja Kalianget jatuh cinta kepada Layonsari, istri Jayaprana dan ingin memilikinya. Kisah dalam opera ini berakhir tragis ketika semua saling bunuh dan semua musnah. Keunikan dari cerita ini adalah, diawali dengan suasana kesedihan, katika terjadi wabah penyakit dan berakhir dengan kesedihan pula, ketika semua musnah. Kisah Jayaprana dan Layonsari sarat mengandung pesan-pesan moral. Dalam penggarapan Nyanyian Layonsari digunakan idiom-idiom musik Bali yaitu, kotekan, efek suara kumbang ngisep, dan efek suara kajar. Selain idiom musik Bali, digunakan juga tangga-nada sintetis Sembilan-nada yang bersumber dan terinspirasi dari laras pelog dan laras slendro. Unsurunsur musik diolah berdasarkan pemahaman teori musik Barat. Melalui pementasan Opera ini diharapkan dapat menyampaikan pesan yang terkandung di dalam cerita dan bisa dimengerti oleh audiens. Selain itu penciptaan Opera Nyanyian Layonsari ini dapat memunculkan gaya musikal yang khas dan dapat digunakan sebagai pengembangan bidang komposisi musik di Indonesia dan dapat dimunculkan di forum internasional.